2020
DOI: 10.1051/e3sconf/202021804024
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of remote sensing extraction methods for glacier firn line-considering Urumqi Glacier No.1 as the experimental area

Abstract: In mid-latitude glaciers, the altitude of the snowline at the end of the ablating season can be used to indicate the equilibrium line, which can be used as an approximation for it. In this paper, Urumqi Glacier No.1 was selected as the experimental area while Landsat TM/ETM+/OLI images were used to analyze and compare the accuracy as well as applicability of the visual interpretation, Normalized Difference Snow Index, single-band threshold and albedo remote sensing inversion methods for the extraction of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Regarding the robustness of the albedo method applied to Urumqi Glacier No. 1, Zhao et al [58] evaluated the performance and accuracy of using visual interpretation, the normalized difference snow index, a single-band threshold, and the albedo method to extract end-of-summer SLA in comparison with the annual ELA. Their results showed that the albedo method was more consistent with the annual ELA obtained from field measurements, except for visual interpretation.…”
Section: Advantages Drawbacks and Robustness Of The Albedo Methods Applied To Mountain Glaciersmentioning
confidence: 99%
“…Regarding the robustness of the albedo method applied to Urumqi Glacier No. 1, Zhao et al [58] evaluated the performance and accuracy of using visual interpretation, the normalized difference snow index, a single-band threshold, and the albedo method to extract end-of-summer SLA in comparison with the annual ELA. Their results showed that the albedo method was more consistent with the annual ELA obtained from field measurements, except for visual interpretation.…”
Section: Advantages Drawbacks and Robustness Of The Albedo Methods Applied To Mountain Glaciersmentioning
confidence: 99%